RACIAL INTERACTION IN JAMES FENIMORE COOPER'S THE LAST OF THE MOHICAN : A GENETIC STRUCTURALISM APPROACH - WIJAYANTI, SRI (2007)
The objective of the research is the novel entitled The Last of The Mohicans by James Fenimore Cooper. The study gives focus on racial interactions as reflected in James Fenimore Cooper's The Last of The Mohicans. The aim of the study is the finding the criticism on racial interaction in social life. The study belongs to a qualitative study. In this method, the researches uses two data source and object of the study is the novel the Last of The Mohicans it self. Meanwhile the secondary ones are any literature related with the study. The technique of data analysis in the study is the descriptive to make an interpretation of the text and content analysis using deductive and inductive method. The result of the study shows the following the conclusion. First, The Last of The Mohicans, James Fenimore Cooper's view on racial interaction in North America in eighteenth century is that solitary human existence needs what is called respect the human right and social interaction in their life. Because by fulfilling both of them, surely they can reach equality between human races. Second, James Fenimore Cooper's view on freedom of life. Freedom is right to act and speak freely for specifically to have their own land and to live in their own land not in the reservation. The existences of rule of reservation are forms of limitations of a freedom. In other words, Cooper want to say that the existence of rule of reservation to be broken, because by doing that people can know which is wrong and right then the result, they are to be more respectfully to the human right in every step. Finally, recognition of equal about human right and the freedom of life ii very important for every tribe as long as they have courage to take the charge of what they have done.